Prevalence of low levels of Vitamin D in patients with osteopenia and osteoporosis. Popayán, Colombia - García-Giraldo, Ana María; Vargas-Uricoechea, Hernando; Potosí-García, Jorge Andrés; Santiago-Ausecha, Daniel Ricardo (Universidad y Salud, 2021)
Introduction: Vitamin D has gained interest because it is a hormone whose low levels are associated with different pathologies such as bone mass disorders. Objective: To determine the prevalence of low levels of vitamin D in adult patients with osteopenia and osteoporosis who received care at an outpatient endocrinology clinic in Popayan, Cauca. Materials and methods: A retrospective and descriptive study that included patients diagnosed with osteopenia and osteoporosis through bone densitometry between 2013 and 2016, who also had their vitamin D levels measured by means of any laboratory method. Sociodemographic characteristics, bone densitometry results as well as vitamin D, parathormone and ionic calcium levels were described. Results: A total of 300 patients with osteopenia and osteoporosis were included in the study, of which 211 had low levels of vitamin D, representing a prevalence of 71.3%. Finally, the average level of 25-hydroxyvitamin D was 24.35 ng/ml. Conclusion: The high prevalence of low levels of vitamin D in patients with osteopenia and osteoporosis highlights the importance to measure 25-hydroxyvitamin D levels in this population in order to carry out an appropriate therapeutic intervention.